A cross‐country comparison of pregnant women's decision‐making and perspectives when opting for non‐invasive prenatal testing in the Netherlands and Belgium. (17th February 2023) - Lannoo, Lore; van der Meij, Karuna R. M.; Bekker, Mireille N.; De Catte, Luc; Deckers, Sarah; Devriendt, Koenraad; Roggen, Nele; Galjaard, Robert‐Jan H.; Gitsels‐van der Wal, Janneke; Macville, Merryn V. E.; Martin, Linda; Sistermans, Erik A.; et al.
Abstract: Background: The Netherlands and Belgium have been among the first countries to offer non‐invasive prenatal testing (NIPT) as a first‐tier screening test. Despite similarities, differences exist in counseling modalities and test uptake. This study explored decision‐making and perspectives of pregnant women who opted for NIPT in both countries. Methods: A questionnaire study was performed among pregnant women in the Netherlands (NL) ( n  = 587) and Belgium (BE) ( n  = 444) opting for NIPT, including measures on informed choice, personal and societal perspectives on trisomy 21, 18 and 13 and pregnancy termination. Results: Differences between Dutch and Belgian women were shown in the level of informed choice (NL: 83% vs. BE: 59%, p  < 0.001), intention to terminate the pregnancy in case of confirmed trisomy 21 (NL: 51% vs. BE: 62%, p  = 0.003) and trisomy 13/18 (NL: 80% vs. BE: 73%, p  = 0.020). More Belgian women considered trisomy 21 a severe condition (NL: 64% vs. BE: 81%, p  < 0.001). Belgian women more frequently indicated that they believed parents are judged for having a child with trisomy 21 (BE: 42% vs. NL: 16%, p  < 0.001) and were less positive about quality of care and support for children with trisomy 21 (BE: 23% vs. NL: 62%, p  < 0.001). Conclusion: Differences in women's decision‐making regarding NIPT and the conditions screened for may be influenced by counseling aspects and country‐specific societal and cultural contexts. Key points: What is already known? Informed choice is considered important when deciding whether or not to participate in prenatal screening to ensure reproductive autonomy. Non‐invasive prenatal testing (NIPT) implementation in various countries reveals striking similarities and differences What does this study add? Level of informed choice for screening with NIPT differs between Dutch (83%) and Belgian women (59%). Societal, cultural and counseling aspects may impact pregnant women's perspectives and decision‐making on prenatal screening with NIPT.